Sexual quality of life in women with multiple sclerosis - Lew-Starowicz, Michał; Rola, Rafał (Menopause Review/Przegląd Menopauzalny, 2012)
Aim of the study : To evaluate sexual functioning and sexual quality of life in women with multiple sclerosis (MS) and to investigate how it is correlated with the occurrence of sexual dysfunctions. Material and methods : We have investigated women with definite multiple sclerosis. The data were obtained through an interview, self-administered questionnaires including the Female Sexual Function Questionnaire (SFQ28) and the Sexual Quality of Life Questionnaire – Female Version (SQoL-F), and neurological examination using the Expanded Disability Status Scale (EDSS). Appropriate analyses were performed to investigate the differences between subgroups and relevant correlations. Results : 137 women at the mean age of 50.7, with MS duration of 16.4 years and EDSS score of 5.2 have completed the study. The most common sexual dysfunctions were hypoactive sexual desire, arousal and orgasmic dysfunctions. They were much more prevalent in comparison to the general population of Polish women. The mean SQoL-F score was 63.4 and it was much higher in women who assessed their relationship with the partner positively. A strong positive correlation between the occurrence of a particular sexual dysfunction, sexual and relationship enjoyment and the sexual quality of life was found. Conclusions : The study indicates that sexual dysfunctions are much more prevalent in MS women and confirms an important influence of sexual dysfunctions on their sexual quality of life. Preserving a good relationship with the partner is a significant factor that improves sexual functioning and quality of life irrespective of the degree of neurological impairment. This should be taken into account when considering therapeutic solutions in MS female patients.